Severity of Pediatric COVID-19: Role of Vitamin D - Nassar, May Fouad; Allam, Mohamed Farouk; ElKhayat, Samer Hamed; Darwish, Yasser Wagih; Shata, Mennatallah Osama (Journal of Pediatric Infectious Diseases, 2022)
Objective Vitamin D has many immune benefits and because its deficiency impacts most age groups, it became a nutrient of interest in the coronavirus disease 2019 (COVID-19) era. The objective of this study was to highlight the contribution of vitamin D status to the disease severity of hospitalized pediatric patients suffering from COVID-19 infection.Methods This was a cross-sectional study that was conducted on 42 children with documented positive polymerase chain reaction for COVID-19 infection. Detailed history taking and thorough clinical examination were done for each recruited patient. Besides the laboratory and radiological assessment done for COVID-19 patients, 25 hydroxy vitamin D levels [25(OH) D] in the serum were estimated using enzyme linked immunosorbent assay.Results Using the cutoff level of 10 ng/mL, only 40% of the patients were below this level and 60% had their vitamin D level more than or equal to 10 ng/mL. Significantly more patients of the first group needed oxygen support (denoting more severe COVID-19 infection and lung involvement). The older the patients, the more evident was vitamin D deficiency among them, and 25(OH) D values were not correlated to weight for length nor weight categories in the studied series of patients suffering from COVID-19.Conclusion Vitamin D deficiency affects the severity of pediatric COVID-19 infection in hospitalized patients. It is prudent to advise vitamin D level assessment in such cases and promptly manage the patients accordingly. We recommend further studies to assess the effect of vitamin D supplementation on the clinical outcome of COVID-19 in the pediatric population and other vulnerable groups.
Keywords: children; COVID-19; hydroxy vitamin D; severity; cross-sectional study